What can a home hemodialysis program offer to patients in a nursing home setting? A case series and feasibility analysis. Issue 2 (12th November 2020) - Scarpioni, Roberto; Ricardi, Marco; Manini, Alessandra; Chiappini, Paola; Ballocchi, Laura; Albertazzi, Vittorio; DeAmicis, Sara; Melfa, Luigi; Rocca, Chiara; Valsania, Teresa; Blanco, Valentina; Fenocchio, Chiara
Abstract: Introduction: Over the last decades, the number of elderly patients on dialysis has rapidly grown on account of increased life expectancy, improved care and reduced mortality rate. Therefore, cooperation between geriatricians and nephrologists has become mandatory for co‐managing kidney disease in these patients. Based on renewed interest in home hemodialysis (HHD), elderly patients may benefit from not being transported from their home for therapy. Methods: Here, we report our experience with HHD involving three elderly patients who were followed‐up over a 15‐months period in a nursing home. Findings: Our experience demonstrates that hospitalization abruptly dropped from 40 days to zero days, the need for erythropoietin stimulating agents (ESAs) diminished, transportation‐related costs for home treatments decreased, and quality of life (QoL) improved. This was confirmed by a questionnaire administered to our patients at the start and again after 6 months of HHD which evaluated the Physical Health Component Score (PCS) and the Mental Health Component Score (MCS). Discussion: Home hemodialysis may represent an important way to improve social, mental, and physical recovery, while also eliminating the cost of transportation and the discomfort of abandoning their "homes" and daily habits. Home hemodialysis is an effective alternative to in‐center HD or peritoneal dialysis (PD) that should be offered to elderly patients when a home caregiver is not available, nonetheless, nursing assistance is required. Moreover, HHD allows patients to stay at home, thereby avoiding several weekly trips to the dialysis center, and may be useful in reducing infections, especially in times of the COVID‐19 pandemic, as demonstrated by our experience.